Pembelajaran Menulis Puisi di Sekolah Menengah Atas - Sutikno Sutikno; Retno Winarni; Suyitno Suyitno; Nugraheni Eko Wardani (Jurusan Tadris Bahasa Indonesia, 2020)
This study aims to describe learning to write poetry in high schools in Brebes Regency. (1) the importance of developing learning to write poetry for high school students that is attractive and fun, (2) the importance of the dimensions of the knowledge construction process in the learning process, (3) there is no model deemed appropriate for learning to write poetry, (4) the importance of the media used in learning to write poetry for high school students, and (5) the importance of introducing students to multiculturalism in learning to write poetry. Things that are needed by teachers and students in learning to write poetry include: (1) easy-to-use media, (2) an interesting and fun learning atmosphere, (3) can develop students' talents and interests, (4) can increase social feelings between friends, and (5) can train courage and self-confidence.Penelitian ini bertujuan untuk mendeskripsikan pembelajaran menulis puisi di SMA se-Kabupaten Brebes. (1) pentingnya pengembangan pembelajaran menulis puisi siswa SMA yang menarik dan menyenangkan, (2) pentingnya dimensi The knowledge construction process dalam proses pembelajaran, (3) belum adanya model yang dianggap tepat untuk pembelajaran menulis puisi, (4) pentingnya media yang digunakan dalam pembelajaran menulis puisi siswa SMA, dan (5) pentingnya mengenalkan kepada siswa tentang multikultural dalam pembelajaran menulis puisi. Hal yang diperlukan guru dan siswa pada pembelajaran menulis puisi, meliputi: (1) media yang mudah digunakan, (2) suasana pembelajaran yang menarik dan menyenangkan, (3) dapat mengembangkan bakat dan minat siswa, (4) dapat meningkatkan rasa sosial antarteman, dan (5) dapat melatih keberanian dan percaya diri.